PERANCANGAN APLIKASI KEARSIPAN SURAT MENYURAT PADA BADAN PEMERINTAHAN (STUDI KASUS : BADAN PEMBERDAYAAN PEREMPUAN PERLINDUNGAN ANAK DAN KELUARGA BERENCANA PONTIANAK) - Eva Meilinda (Universitas Bina Sarana Informatika, 2016)
BP3AKB is Women Empowerment, Child Protection and Family Planning. BP3AKB is a government agency that houses various issues of protection of women and children. Currently, government agencies are experiencing problems to records. Archive storage is done on BP3AKB still done manually, recording in ledgers and records physical form does not neatly arranged. This causes the data of incoming mail or outgoing mail lost and damaged, thus the researchers designed an archiving application that can solve basic problems that occur in BP3AKB. This application was designed using descriptive methods and techniques of data collection. In addition, researchers also makes system modeling using UML and editor Visual Basic 6.0 and MySQL as data storage. With the application of this filing, it is expected that the data can be stored properly, neatly and correctly.Keywords: Archive Aplication, Archive Aplication Design, BP3AKB